Efficient Phase-Field Modeling of Quasi-Static and Dynamic Crack Propagation Under Mechanical and Thermal Loadings - Lotfi Ben Said; Hamdi Hentati; Mohamed Turki; Alaa Chabir; Sattam Alharbi; Mohamed Haddar (Mathematics)
The main objective of this work was to model the failure mechanisms of brittle materials subjected to thermal and mechanical loads. A diffusive representation of the crack topology provides the basis for the regularized kinematic framework used. With a smooth transition from the undamaged to the fully damaged state, the fracture surface was roughly represented as a diffusive field. By integrating a staggered scheme and spectral decomposition, the variational formulation was used after being mathematically written and developed. Its effectiveness was analyzed using extensive benchmark tests, demonstrating the effectiveness of the phase-field model in modeling the behavior of brittle materials. This proposed approach was experimentally tested through the examination of crack propagation paths in brittle materials that were subjected to variable mechanical and thermal loads. This work focused on the integration of a spectral decomposition-based phase-field model with thermo-mechanical coupling for dynamic fracture, supported by benchmark validation and the comparative assessment of energy decomposition strategies. The results highlight the accuracy and robustness of numerical and experimental methodologies proposed to model fracture mechanics in brittle materials subjected to complex loading conditions.